1959
DOI: 10.1111/j.1471-4159.1959.tb13334.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Catechol‐o‐methyl Transferase in the Nervous System and Other Tissues

Abstract: O-METHYLATION has been shown to be the principal pathway for the metabolism of administered adrenaline and noradrenaline (AXELROD, INSCOE, SENOH and WITKOP, 1958; LABROSE, AXELROD and K m , 1958). An enzyme, catechol-0-methyl transferase (COMT),? which catalyses the transfer of a methyl group from S-adenosylmethionine to the 3-hydroxy group of catechois, has been described (AXELROD 1957; AXFLROD and TOMCHICK, 1958). Since the products, metanephrine (3-0-methyladrenaline) and normetanephrine (3-O-methylnoradre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
2

Year Published

1963
1963
1994
1994

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(43 citation statements)
references
References 10 publications
(1 reference statement)
1
40
2
Order By: Relevance
“…The highest COMT enzyme activity has been found in the liver, followed by the submaxillary and parotid glands, pancreas, adenohypophysis, neurohypophysis, different brain areas, peripheral nerves and ganglia, and blood vessels (Axelrod et al, 1959). Despite the relatively wide and abundant distribution of the enzyme in rat tissues, the exact cellular localization of COMT is not completely known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest COMT enzyme activity has been found in the liver, followed by the submaxillary and parotid glands, pancreas, adenohypophysis, neurohypophysis, different brain areas, peripheral nerves and ganglia, and blood vessels (Axelrod et al, 1959). Despite the relatively wide and abundant distribution of the enzyme in rat tissues, the exact cellular localization of COMT is not completely known.…”
Section: Introductionmentioning
confidence: 99%
“…1975;Axelrod et al, 1959). Intense staining was also observed in kidneys, in which COMT activity is high (Guldberg and Marsden, 1975;Ax'elrod and Tomschik, 1958).…”
mentioning
confidence: 99%
“…COMT is important in the enzymatic inactivation of circulating catecholamines (27,28), catecholamines released as neurotransmitters from both central and peripheral catecholamine containing neurons (9,18,24), xenobiotic catechols (3,14), and catecholestrogens (6,15). COMT activity is widely distributed in mammalian tissues (17,18) and has been clearly demonstrated in splenic tissue (1,2,19) and in erythrocytes (32,42). Biochemical studies indicate that COMT is present almost exclusively as a soluble cytoplasmic protein with a molecular size of 23000 Daltons (7,8) although several investigators have reported the presence of small amounts of membrane-bound COMT activity (7).…”
Section: Catechol-o-methyltransferasementioning
confidence: 99%
“…The AChE fmdings will be reported elsewhere as a part 01" a more detailed paper. HIOMT activity in the pineal gland was determined by measuring the formation of melatonin methyl-14C produced from S-adenosylmethionine-methyl-14C and N -acetylserotonin, employing the procedure as reported by Axelrod et al (1961)_ RESULTS Experimental groups did not differ on emotionality rating either after 35 days or after 70 days in rearing conditions. However, significant differences in body weight were obtained for different groups, as evident in Table 1, which shows body weight for all experimental groups for four weighing periods.…”
Section: Effect Of Visual Pattern Restriction In Earlymentioning
confidence: 99%